Nutrition Care in Cancer Patients - Nenni Dwi Aprianti Lubis; Ridwan Balatif (Majalah Kedokteran Andalas, 2021)
Objectives: to provide information about nutritional problems in cancer patients. Method: writing this article using the literature searching method. The sources used are articles, books and the WHO website to collect epidemiological data. Articles and books are taken in Indonesian and English. Search the source of the article using the help of Google Scholar and Google search engines. Results: about 25-70% of patients with cancer are malnourished, this is related to changes in metabolism. Changes in carbohydrate metabolism such as an increase in lactate metabolism 10-100 times faster. Changes in protein metabolism such as protein degradation in muscle. Changes in fat metabolism such as increased lipolysis by 85%. These metabolic changes must be prevented by providing adequate nutrition for patients with cancer. Malnutrition in patients with this cancer can increase the length of stay and increase mortality. With the provision of adequate nutritional therapy is expected to help accelerate the healing process of patients with cancer. Conclusion: Malnutrition in patients with cancer is a condition that often occurs and can have an impact on increasing patient mortality. Provision of adequate nutritional therapy is expected to reduce the risk of mortality and accelerate the healing of patients with cancer.